Caracterización de pasivos ambientales mineros en la microcuenca de la quebrada campanas de la parroquia San Carlos de las minas, cantón Zamora y provincia de Zamora Chinchipe. - Enriquez Sánchez, Jessy Jamiley (2018)
This research project presents a baseline of mining environmental liabilities resulting from mining activities within the microbasin of the Quebrada Campanas, located in the San Carlos de las Minas parish, cantón Zamora and Zamora Chinchipe province; conformed by 1755.67 hectares. It has been developed with the purpose of determining environmental pollution on water, soil and air in areas that are of high importance or negatively impact the environment, as well as proposing the respective measures of remediation, mitigation and correction to these affectations. First, the environmental situation was developed, resulting in information on both the physical, biotic and socioeconomic, cultural and aesthetic environments. Within the physical environment, the microbasin has the Campanas creek as its main tributary, whose length is 8.9 kilometers and is fed by several natural streams. The microbasin covers mainly strong slopes with 40 - 50% inclination, is characterized by presenting soils of order inceptisol; characterized geologically by presenting volcanic rocks from the Zamora batholith, rocks metamorphosed by Skarn and in the form of a flat valley colluvium - alluvial material. In addition, land use in general is agricultural and livestock. Within the floristic species that prevail in the place are the plants of Guarumo (Cecropia andina cuatrec), Palma (Geonoma weberbaueri) and elephant grass (Pennisetum purpureum schumach). Registered fauna is scarce because many of the species are immersed in the vegetation and its observation is difficult. However, the primate family found is the highlight in this section. For the analysis of the socio-economic, cultural and aesthetic environment, the population of San Carlos de las Minas was considered, which comprises a total of 2,180 inhabitants, of which the majority are engaged in mining, agricultural and livestock activities. Also, children and young people work in primary, secondary and university education. Subsequently, the identification and characterization of mining environmental liabilities was carried out through field visits to the mining concessions that cover the study area. The environmental liabilities were assessed using the methodology that determines the degree of importance on the receiving environment, obtaining a baseline of 13 environmental liabilities, of which 10 are of medium importance and the remaining 3 are of high importance. After the identification, characterization, valuation of environmental mining liabilities, the proposal of environmental programs is carried out towards the impacts caused in the components water, soil and air. whose programs contain remedial, mitigating and corrective measures on the physical, biotic and socioeconomic, cultural and aesthetic.